Determinación de la eficiencia del carbón activado obtenido experimentalmente a partir de residuos agrícolas del Alto Mayo - Terrones Vásquez, Yeltsin Richelly (2014)
The present thesis work entitled " Efficiency determination of the of the activated carbon obtained experimentally from the Alto Mayo agricultura} residues", it has been realized by the purpose of obtaining activated coal and hereby to give a value added to the agricultura} residues, since the raw material used for the obtaining of the final product they are: coconut rinds, coffee and cocoa. The project developed was explanatory type, where teams were used and materials available to the ecology faculty- Biology and Chemistry Laboratory. This work has as objective: to determine the efficiency of the activated carbon adsorption processes by means of the methylene blue solution. For it the analysis of the characteristics became initially physicist - chemistry of the samples ( dampness %, fixed carbon %, total ashes %, porosity % and volatile matter % ). In addition analysis was carried out in the evaluated variables that influence the obtaining of the activated carbon and during the adsorption process. Inside the variables it was considered to be the carbonization temperature - activation of the sample, being changed from 550°C, 600°C, 650°C, 700°C, 750°C. In addition as analysis extras in the adsorption stage, have been changed the contact time of the coal activated with the solution of blue of methylene by times of 1 min, 1:30 min, min, 2:30 min, 3 min and finally made to him change the grams of activated coal added to the blue solution of methylene with weight of0.5 gr, 0.75 gr, gr, 1.25 gr, 1.5 gr. Finally, it is concluded that during the adsorption process is determined that the efficiency of the activated carbon of the coconut husk is at a temperature of 700 oc (85.34% ), time of contact ofthe activated carbon with the methylene blue solution of 1:30 min (85 %) and adding 0.5 gr (85.6% ). The efficiency of the activated carbon from the coffee peel is at a temperature of 650 oc (89.86 %), time of contact of the activated carbon with the methylene blue solution for. 2 min (76.9 %) and adding 1 gr (85.6 %). The efficiency of the activated carbon from the peel of cocoa is at a